Design and psychometric validation of a Customer Analytics Capabilities (CAC) scale: empirical evidence in Colombian organizations - Maya Restrepo, María Alejandra; Pérez Rave, Jorge Iván (Cuadernos de Administración, 2024)
Although the measurement of Customer Analytics Capabilities (CAC) has aroused interest among scholars and entrepreneurs, there is a lack of an instrument that synthesizes the main organizational routines involved in such a construct, based on empirical manifestations provided by scientific literature. The study contributes to closing this gap through the design and psychometric validation of a CAC measurement model. The sample includes survey data from 101 Colombian companies. The source of information corresponds to professionals in marketing or analytics areas. A psychometric analytical framework is used, which incorporates exploratory and confirmatory factor analysis. Two plausible measurement models are obtained: The three-dimensional model consists of 10 items grouped into the factors: customer acquisition analytics capability; customer maintenance analytics capability; and customer economic evaluation analytics capability. This satisfies fit, content validity, convergent and discriminant validity, reliability, and equity criteria. The unidimensional model contains 14 items, it also fulfills psychometric quality requirements, and it is useful when a parsimonious approach to the general attribute of CAC is desired. The developed scales make CAC measurable through a set of routines that reconfigure traditional operational capabilities in marketing. In addition, they facilitate the execution of reliable organizational diagnoses, the definition of work agendas for analytics departments and promote future work on the relationship between CAC and business performance.